Current statistical publications held in the University Of Malaya Library: an annotated list. - Chall, D.K. (University of Malaya Library, 1986)
Lists 18 current sources of statistical information in the field of socio-economics in Malaysia. An abstract of each source is included and detailed tables of contents.